Sex Differences in the HPA Axis. Issue 3 (12th June 2014) - Goel, Nirupa; Workman, Joanna L.; Lee, Tiffany T.; Innala, Leyla; Viau, Victor
Abstract: The hypothalamic‐pituitary‐adrenal (HPA) axis is a major component of the systems that respond to stress, by coordinating the neuroendocrine and autonomic responses. Tightly controlled regulation of HPA responses is critical for maintaining mental and physical health, as hyper‐ and hypo‐activity have been linked to disease states. A long history of research has revealed sex differences in numerous components of the HPA stress system and its responses, which may partially form the basis for sex disparities in disease development. Despite this, many studies use male subjects exclusively, while fewer reports involve females or provide direct sex comparisons. The purpose of this article is to present sex comparisons in the functional and molecular aspects of the HPA axis, through various phases of activity, including basal, acute stress, and chronic stress conditions. The HPA axis in females initiates more rapidly and produces a greater output of stress hormones. This review focuses on the interactions between the gonadal hormone system and the HPA axis as the key mediators of these sex differences, whereby androgens increase and estrogens decrease HPA activity in adulthood. In addition to the effects of gonadal hormones on the adult response, morphological impacts of hormone exposure during development are also involved in mediating sex differences. Additional systems impinging on the HPA axis that contribute to sex differences include the monoamine neurotransmitters norepinephrine and serotonin. Diverse signals originating from the brain and periphery are integrated to determine the level of HPA axis activity, and these signals are, in many cases, sex‐specific. © 2014 American Physiological Society. Compr Physiol 4:1121‐1155, 2014.